The Presidential Threshold Dilemma: Constitutional Legitimacy Versus Democratic Erosion in Indonesia - Amiruddin; Mislia; Mateu, William (International Journal of Law and Society, 2025)
The background of this research stems from the tension that arises between the formal legitimacy of the presidential threshold and its impact on substantive representation of the people. This research examines the presidential threshold in Indonesia's 2024 simultaneous general elections with the main objectives: (a) to analyse its constitutional basis explicitly and (b) to evaluate its impact on political representation and democratic inclusiveness. The method employed is a normative juridical approach, which involves analysing primary legal materials, including the 1945 Constitution, particularly Article 6A, Law No. 7 of 2017 concerning General Elections, and related decisions of the Constitutional Court. The research findings reveal a crucial dilemma: first, although the threshold has a legitimate legal basis and is a valid legislative policy, its legitimacy is formalistic in nature. Second, its implementation substantially reduces political representation; the 2019 Election data show that parties representing 34.2% of the popular vote cannot participate in the presidential contest, resulting in forced joining coalitions that are often at odds with the aspirations of their constituents. This situation erodes popular sovereignty and contradicts the Pancasila value of social justice, exposing a fundamental tension between the legal form and substance of democracy. The originality of this research lies in its systematic presentation of this representation gap and its normative contribution, proposing a new threshold model of 10–15% to balance political stability with democratic inclusiveness. The implications are practical for policymakers and the General Elections Commission (KPU), as well as theoretical for the global discourse on electoral system design in developing democracies. A limitation of this research is its normative nature, necessitating further empirical studies on voter behaviour and the impact of digital campaigns.